The Improvement of Students Mathematical Understanding and Self-Concept through a Discovery Learning Model - T. Mahmudi; M. Ikhsan; Rahmah Johar (Proceedings of AICS - Social Sciences, 2018)
One of the competencies which students must possess is a mathematical understanding. Another aspect that supports understanding is self-concept. An effort that can be taken as a solution for improving students’ understanding and the self-concept is a model of learning which can lead students to find their concept. This model is often called discovery learning. This study aims to improve students’ mathematical understanding and the self-concept through the discovery learning model. In this study, the researcher used quantitative research. The population of this study was all senior high school Ulumuddin students in the 2016/2017 school year. The sample of this study was 40 students in grade 10 who were randomly chosen from two classes. The data in this study were obtained using instruments compiled in the form of questionnaires and tests that were answered by the respondents. The results showed that the improvement of students’ mathematical understanding and self-concept who obtained learning with the discovery learning model was better than students who gain learning without using the model of Discovery Learning. However, there was no interaction between the model and the levels of understanding and the self-concept of students.Keywords: mathematical understanding, self-concept, discovery learning.